Impact of Operations Analysis on Productivity in Small Textile Manufacturing Businesses in Imbabura, Ecuador - Yépez M, Rolando Ismael; Flores Torres, Diego Iván; Benítez Pereira, Juan Patricio; Ormaza Morejón, Maricela Fernanda (Universidad Francisco de Paula Santander, 2024)
The effects of the introduction of operations analysis in clothing assembly activities in a small company in the Antonio Ante canton of the province of Imbabura are studied. The methodological framework followed is the achievement of the following steps: 1) the selection of the manufacturing operations, 2) the selection of the participants, 3) the measurement of the initial state of the operations, 4) the systematic analysis of the operations and, 5) the improvement proposal. The introduction of operations analysis represents an estimated decrease of 18 seconds in cycle time, which translates into an increase in productivity by 15.79%. Such effects position operations analysis as a methodology applicable to the clothing company, which generates a positive impact on its usual factory work procedures.